The Warburg effect then and now: From cancer to inflammatory diseases - Palsson-McDermott, Eva M.; O'Neill, Luke A. J. (BioEssays, 2013)
Inflammatory immune cells, when activated, display much the same metabolic profile as a glycolytic tumor cell. This involves a shift in metabolism away from oxidative phosphorylation towards aerobic glycolysis, a phenomenon known as the Warburg effect. The result of this change in macrophages is to rapidly provide ATP and metabolic intermediates for the biosynthesis of immune and inflammatory proteins. In addition, a rise in certain tricarboxylic acid cycle intermediates occurs notably in citrate for lipid biosynthesis, and succinate, which activates the transcription factor Hypoxia‐inducible factor. In this review we take a look at the emerging evidence for a role for the Warburg effect in the immune and inflammatory responses. The reprogramming of metabolic pathways in macrophages, dendritic cells, and T cells could have relevance in the pathogenesis of inflammatory and metabolic diseases and might provide novel therapeutic strategies. Recent studies reveal that inflammatory cells, when activated, display similar metabolic traits as cancer cells. During an inflammatory response or infection pro‐inflammatory immune cells can shift their metabolism away from oxidative phosphorylation towards a high rate of glycolysis, a phenomenon known as the Warburg effect.